Kimia Fisik Perairan dan Ektoparasit Ikan Nila dan Patin Di Situ Gintung, Tangerang Selatan, Banten - Haribowo, Dinda Rama; Annisa, Syifa; Kholidah, Nur; Izza, Nia Dzirwatul; Zahrah, Pratiwi Amalia; Pamungkas, Ario Putro; Ramadhan, Firdaus; Rijaluddin, Alfan Farhan; Assuyuti, Yayan Mardiansyah (Journal of Marine and Aquatic Sciences; Vol 5 No 2 (2019)DO - 10.24843/jmas.2019.v05.i02.p06, 2019)
Poor water quality based on physical and chemical waters is one of the factors that influence the infection and presence of fish ectoparasites. The aim of study was to determine the physical and chemical waters, the types and prevalence of ectoparasites and the correlation of ectoparasites with physical and chemical waters. The study was conducted in Situ Gintung, South Tangerang from March to June 2018 with samples from Floating Net Cages (KJA) and fishing. The results showed that the physical and chemical waters generally within standard quality for fish cultivation. The number and type of fish ectoparasites consist of Trichodina sp., Chilodonella sp., Litonotus sp., Vorticella sp., Dactylogyrus sp. and Capillaria sp. Based on the Canonical Correspondence Analysis (CCA) shows that ectoparasites are affected by physical and chemical waters.